Influence of Data Mining and Data Warehouse on Strategic Planning: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2022)
Users can access their data in today's  reporting environment, but it does not address all of their  issues. The people have access to the statistics, but they  cannot ensure the data's truthfulness or the speed with  which it is returned. Data warehousing addresses the  aforementioned issues by providing technology that allows  users or decision makers to analyze large amounts of data in  a short period of time. Data warehousing allows users to  extract information in real time, which assists them in  making decisions. Many businesses wish to utilize the  information for additional reasons. As a result, methods for  mining fresh information from data warehouses have  developed. Data collection and data excavation provide the  groundwork for developing choice provision and decision making information system tools that track an  organization's progress concerning its objectives. Data mining and warehousing are technologies that allow a user  in the business sector or government to analyze large  amounts of data and make choices that benefit the whole  organization. This article uses appropriate graphics to  explain the impression, benefits, and drawbacks of data  mining and warehousing. The duties and responsibilities of  data warehousing organizational members are also  addressed in this article. To sum up, we're attempting to  demonstrate how “Data Mining (DM) & Date Warehouses  (DW)" may be utilized in companies, how data can aid  making decisions, and how managers can conduct extra precise, meaningful, and consistent analysis using their  data.
Keywords: Data Marts; Data Mining; Data Warehousing; Knowledge Discovery; Staging Layer